Assessing the rational use of cefotaxime at Queen Elizabeth ll Hospital - Maphasa, Teboho (My University, 2004)
The purpose of the study was to evaluate the use of cefotaxime with the idea of improving its use within the hospital. Improving the use of cefotaxime could result in a change in the proportion spent from the pharmacy budget. More importantly a change in prescribing patterns of this drug could also result in a reduction in resistant patterns of cefotaxime.
A RESEARCH REPORT SUBMITTED TO THE FACULTY OF HEALTH SCIENCES, UNIVERSITY OF WITWATERSRAND, JOHANNESBURG, IN PARTIAL FULFILMENT OF THE REQUIREMENTS FOR THE DEGREE OF MASTER OF PHARMACY IN CLINICAL PHARMACY 2004
Keywords: Cefotaxime; Hospitals; Lesotho; Anti-Infective Agents